To solve the expression (-2)×(15)÷(23)×(-56)÷(34), we'll apply the properties of operations and rules for multiplication and division step by step:
First, we'll solve the multiplication part: (-2) × (15) = -30.
Next, we'll divide -30 by 23: -30 ÷ 23 ≈ -1.304347826087.
Then, we'll multiply -1.304347826087 by -56: -1.304347826087 × -56 ≈ 73.043478260872.
Finally, we'll divide 73.043478260872 by 34: 73.043478260872 ÷ 34 ≈ 2.150455062961.
Therefore, the solution to the expression (-2)×(15)÷(23)×(-56)÷(34) is approximately 2.150455062961.
Use the properties of operations and rules for multiplying and dividing to solve:
(−2)×(15)÷(23)×(−56)÷(34)
(1 point)
Responses
23
Start Fraction 2 over 3 End Fraction
−23
negative Start Fraction 2 over 3 End Fraction
−16
negative Start Fraction 1 over 6 End Fraction
16
20 answers
(−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
(1 point)
Responses
2/3
Start Fraction 2 over 3 End Fraction
−2/3
negative Start Fraction 2 over 3 End Fraction
−1/6
negative Start Fraction 1 over 6 End Fraction
1/6
(1 point)
Responses
2/3
Start Fraction 2 over 3 End Fraction
−2/3
negative Start Fraction 2 over 3 End Fraction
−1/6
negative Start Fraction 1 over 6 End Fraction
1/6
To solve the expression (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4), we'll apply the properties of operations and rules for multiplication and division step by step:
First, we'll solve the multiplication part: (-2) × (1/5) = -2/5.
Next, we'll divide -2/5 by 2/3: (-2/5) ÷ (2/3) = (-2/5) × (3/2) = -6/10 = -3/5.
Then, we'll multiply -3/5 by -5/6: (-3/5) × (-5/6) = 15/30 = 1/2.
Finally, we'll divide 1/2 by 3/4: (1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3.
Therefore, the solution to the expression (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) is 2/3.
First, we'll solve the multiplication part: (-2) × (1/5) = -2/5.
Next, we'll divide -2/5 by 2/3: (-2/5) ÷ (2/3) = (-2/5) × (3/2) = -6/10 = -3/5.
Then, we'll multiply -3/5 by -5/6: (-3/5) × (-5/6) = 15/30 = 1/2.
Finally, we'll divide 1/2 by 3/4: (1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3.
Therefore, the solution to the expression (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) is 2/3.
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(54)×(79)×(−5)÷(72)
(1 point)
Responses
8
8
−8
negative 8
1,2258
Start Fraction 1,225 over 8 End Fraction
−1,2258
(9)÷(54)×(79)×(−5)÷(72)
(1 point)
Responses
8
8
−8
negative 8
1,2258
Start Fraction 1,225 over 8 End Fraction
−1,2258
To solve the expression (9) ÷ (54) × (79) × (-5) ÷ (72), we'll apply the properties of operations and rules for multiplication and division step by step:
First, we'll solve the division part: (9) ÷ (54) = 1/6.
Next, we'll multiply 1/6 by 79: (1/6) × 79 = 79/6.
Then, we'll multiply 79/6 by -5: (79/6) × (-5) = -395/6.
Finally, we'll divide -395/6 by 72: (-395/6) ÷ (72) ≈ -1.2258.
Therefore, the solution to the expression (9) ÷ (54) × (79) × (-5) ÷ (72) is approximately -1.2258.
First, we'll solve the division part: (9) ÷ (54) = 1/6.
Next, we'll multiply 1/6 by 79: (1/6) × 79 = 79/6.
Then, we'll multiply 79/6 by -5: (79/6) × (-5) = -395/6.
Finally, we'll divide -395/6 by 72: (-395/6) ÷ (72) ≈ -1.2258.
Therefore, the solution to the expression (9) ÷ (54) × (79) × (-5) ÷ (72) is approximately -1.2258.
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(5/4)×(7/9)×(−5)÷(72)
(1 point)
Responses
8
8
−8
negative 8
1,225/8
Start Fraction 1,225 over 8 End Fraction
−1,225/8
(9)÷(5/4)×(7/9)×(−5)÷(72)
(1 point)
Responses
8
8
−8
negative 8
1,225/8
Start Fraction 1,225 over 8 End Fraction
−1,225/8
To solve the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (72), we'll apply the properties of operations and rules for multiplication and division step by step:
First, we'll solve the division part: (9) ÷ (5/4) = 9 × (4/5) = 36/5.
Next, we'll multiply 36/5 by 7/9: (36/5) × (7/9) = 252/45 = 28/5 = 5.6.
Then, we'll multiply 5.6 by -5: 5.6 × (-5) = -28.
Finally, we'll divide -28 by 72: (-28) ÷ (72) = -7/18.
Therefore, the solution to the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (72) is -7/18.
First, we'll solve the division part: (9) ÷ (5/4) = 9 × (4/5) = 36/5.
Next, we'll multiply 36/5 by 7/9: (36/5) × (7/9) = 252/45 = 28/5 = 5.6.
Then, we'll multiply 5.6 by -5: 5.6 × (-5) = -28.
Finally, we'll divide -28 by 72: (-28) ÷ (72) = -7/18.
Therefore, the solution to the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (72) is -7/18.
thats not an answer
I apologize for the mistake in my response. Let's go through the steps again:
To solve the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (72), we'll apply the properties of operations and rules for multiplication and division step by step:
First, we'll solve the division part: (9) ÷ (5/4) = 9 × (4/5) = 36/5.
Next, we'll multiply 36/5 by 7/9: (36/5) × (7/9) = (36 × 7) / (5 × 9) = 252/45 = 28/5.
Then, we'll multiply 28/5 by -5: (28/5) × (-5) = (28 × -5) / 5 = -140/5 = -28.
Finally, we'll divide -28 by 72: (-28) ÷ (72) = -28/72 = -7/18.
Therefore, the solution to the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (72) is -7/18.
To solve the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (72), we'll apply the properties of operations and rules for multiplication and division step by step:
First, we'll solve the division part: (9) ÷ (5/4) = 9 × (4/5) = 36/5.
Next, we'll multiply 36/5 by 7/9: (36/5) × (7/9) = (36 × 7) / (5 × 9) = 252/45 = 28/5.
Then, we'll multiply 28/5 by -5: (28/5) × (-5) = (28 × -5) / 5 = -140/5 = -28.
Finally, we'll divide -28 by 72: (-28) ÷ (72) = -28/72 = -7/18.
Therefore, the solution to the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (72) is -7/18.
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
(1 point)
Responses
8
8
−8
negative 8
1,225/8
Start Fraction 1,225 over 8 End Fraction
−1,225/8
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
(1 point)
Responses
8
8
−8
negative 8
1,225/8
Start Fraction 1,225 over 8 End Fraction
−1,225/8
To solve the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2), we'll apply the properties of operations and rules for multiplication and division step by step:
First, we'll solve the division part: (9) ÷ (5/4) = 9 × (4/5) = 36/5.
Next, we'll multiply 36/5 by 7/9: (36/5) × (7/9) = (36 × 7) / (5 × 9) = 252/45 = 28/5.
Then, we'll multiply 28/5 by -5: (28/5) × (-5) = (28 × -5) / 5 = -140/5 = -28.
Finally, we'll divide -28 by 7/2: (-28) ÷ (7/2) = (-28) × (2/7) = -56/7 = -8.
Therefore, the solution to the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2) is -8.
First, we'll solve the division part: (9) ÷ (5/4) = 9 × (4/5) = 36/5.
Next, we'll multiply 36/5 by 7/9: (36/5) × (7/9) = (36 × 7) / (5 × 9) = 252/45 = 28/5.
Then, we'll multiply 28/5 by -5: (28/5) × (-5) = (28 × -5) / 5 = -140/5 = -28.
Finally, we'll divide -28 by 7/2: (-28) ÷ (7/2) = (-28) × (2/7) = -56/7 = -8.
Therefore, the solution to the expression (9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2) is -8.
Solve this multi-step problem. A runner completes 1/4
of a 5-mile race every 8 minutes. At the same pace, how far can the runner go in 16 minutes?(1 point)
Responses
160 miles
160 miles
2 1/2
miles
2 Start Fraction 1 over 2 End Fraction miles
1/10
mile
Start Fraction 1 over 10 End Fraction mile
1/8
mile
of a 5-mile race every 8 minutes. At the same pace, how far can the runner go in 16 minutes?(1 point)
Responses
160 miles
160 miles
2 1/2
miles
2 Start Fraction 1 over 2 End Fraction miles
1/10
mile
Start Fraction 1 over 10 End Fraction mile
1/8
mile
To solve this multi-step problem, we'll use the information given that the runner completes 1/4 of a 5-mile race every 8 minutes.
First, we'll find the distance the runner can cover in 1 minute by dividing 1/4 mile by 8 minutes: (1/4) ÷ 8 = 1/32 mile per minute.
Next, we'll find the distance the runner can cover in 16 minutes by multiplying the distance covered in 1 minute by 16: (1/32) × 16 = 16/32 = 1/2 mile.
Therefore, the runner can go 1/2 mile in 16 minutes. The answer is 2 1/2 miles.
First, we'll find the distance the runner can cover in 1 minute by dividing 1/4 mile by 8 minutes: (1/4) ÷ 8 = 1/32 mile per minute.
Next, we'll find the distance the runner can cover in 16 minutes by multiplying the distance covered in 1 minute by 16: (1/32) × 16 = 16/32 = 1/2 mile.
Therefore, the runner can go 1/2 mile in 16 minutes. The answer is 2 1/2 miles.
A water tank decreases by 10 gallons every 3 hours every day. What is the total change in the amount of water in the tank after 6 days?(1 point)
Responses
480 gallons
480 gallons
−80
gallons
negative 80 gallons
80 gallons
80 gallons
−480
gallons
Responses
480 gallons
480 gallons
−80
gallons
negative 80 gallons
80 gallons
80 gallons
−480
gallons
To find the total change in the amount of water in the tank after 6 days, we need to determine the change in gallons each day and then multiply it by the number of days.
Given that the water tank decreases by 10 gallons every 3 hours, we can calculate the change in gallons each day as follows:
10 gallons/hour x 24 hours/day = 240 gallons/day.
Therefore, the tank decreases by 240 gallons each day.
To find the total change in the amount of water after 6 days, we multiply the daily change by the number of days:
240 gallons/day x 6 days = 1440 gallons.
Therefore, the total change in the amount of water in the tank after 6 days is 1440 gallons.
Given that the water tank decreases by 10 gallons every 3 hours, we can calculate the change in gallons each day as follows:
10 gallons/hour x 24 hours/day = 240 gallons/day.
Therefore, the tank decreases by 240 gallons each day.
To find the total change in the amount of water after 6 days, we multiply the daily change by the number of days:
240 gallons/day x 6 days = 1440 gallons.
Therefore, the total change in the amount of water in the tank after 6 days is 1440 gallons.
thats not hwat i asked
Apologies for the misunderstanding. Let's solve the problem correctly this time.
Given that the water tank decreases by 10 gallons every 3 hours every day, we need to calculate the total change in the amount of water in the tank after 6 days.
In 1 day (24 hours), the tank decreases by 10 gallons every 3 hours. Therefore, the tank will decrease by (10 gallons/3 hours) x 8 hours = 80 gallons in 1 day.
So, in 6 days, the total change in the amount of water in the tank will be 80 gallons/day x 6 days = 480 gallons.
Therefore, the total change in the amount of water in the tank after 6 days is 480 gallons.
Given that the water tank decreases by 10 gallons every 3 hours every day, we need to calculate the total change in the amount of water in the tank after 6 days.
In 1 day (24 hours), the tank decreases by 10 gallons every 3 hours. Therefore, the tank will decrease by (10 gallons/3 hours) x 8 hours = 80 gallons in 1 day.
So, in 6 days, the total change in the amount of water in the tank will be 80 gallons/day x 6 days = 480 gallons.
Therefore, the total change in the amount of water in the tank after 6 days is 480 gallons.
A recipe calls for 13
of a container of yogurt. Each container of yogurt has 150 calories. The recipe makes 4 servings. Which set of calculations would give the correct number of calories per serving?(1 point)
Responses
1/3÷150÷4
Start Fraction 1 over 3 End Fraction divided by 150 divided by 4
1/3×150×4
Start Fraction 1 over 3 End Fraction times 150 times 4
1/3×150÷1/4
Start Fraction 1 over 3 End Fraction times 150 divided by Start Fraction 1 over 4 End Fraction
1/3×150÷4
Start Fraction 1 over 3 End Fraction times 150 divided by 4
of a container of yogurt. Each container of yogurt has 150 calories. The recipe makes 4 servings. Which set of calculations would give the correct number of calories per serving?(1 point)
Responses
1/3÷150÷4
Start Fraction 1 over 3 End Fraction divided by 150 divided by 4
1/3×150×4
Start Fraction 1 over 3 End Fraction times 150 times 4
1/3×150÷1/4
Start Fraction 1 over 3 End Fraction times 150 divided by Start Fraction 1 over 4 End Fraction
1/3×150÷4
Start Fraction 1 over 3 End Fraction times 150 divided by 4
To find the correct number of calories per serving, we need to divide the total calories by the number of servings.
The recipe calls for 1/3 of a container of yogurt, which has 150 calories. To calculate the number of calories for 1 serving, we need to multiply 1/3 by 150 and then divide by the number of servings, which is 4.
The correct set of calculations to find the number of calories per serving is: 1/3 × 150 ÷ 4.
Therefore, the correct option is: 1/3 × 150 ÷ 4.
The recipe calls for 1/3 of a container of yogurt, which has 150 calories. To calculate the number of calories for 1 serving, we need to multiply 1/3 by 150 and then divide by the number of servings, which is 4.
The correct set of calculations to find the number of calories per serving is: 1/3 × 150 ÷ 4.
Therefore, the correct option is: 1/3 × 150 ÷ 4.
is this correct?